Peran Transformational Leadership Dalam Meningkatkan Employee Creativity Pada Era Disrupsi - Alfandy Hanson Wicaksono; Roy Setiawan (Poltanesa, 2022)
This study aims to be able to solve the research gap on employee creativity and be able to find out the role of transformational leadership towards employee creativity through trustworthiness in Batik craftsmen in Solo. This research will be conducted in Solo, by taking a sample of 100 batik artisan respondents who have been selected with an average age of 17-55 years, because they have been considered to be able to answer and understand questions widely and more reliably and taken using the purposive sampling method because it is considered a method considered appropriate in this study. The data were quantitatively analyzed using Partial Least Sampling (PLS) which is part of the Structural Equation Marketing (SEM). The results of research conducted by the author have shown that trustworthiness partially has a significant effect on employee creativity in batik craftsmen in Solo. Meanwhile, transformational leadership has no effect on employee creativity; and overall, transformational leadership positively affects employee creativity through trustworthiness.